Proceedings of the 20th ACM International Conference on Multimedia 2012
DOI: 10.1145/2393347.2393439
|View full text |Cite
|
Sign up to set email alerts
|

Discovering informative social subgraphs and predicting pairwise relationships from group photos

Abstract: An increasing number of users are contributing the sheer amount of group photos (e.g., for family, classmates, colleagues, etc.) on social media for the purpose of photo sharing and social communication. There arise strong needs for automatically understanding the group types (e.g., family vs. classmates) for recommendation services (e.g., recommending a family-friendly restaurant) and even predicting the pairwise relationships (e.g., mother-child) between the people in the photo for mining implicit social con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…Several works address investigation of social relations based on such universally valid implicit cues as the age difference between parents and children or the opposite genders of heterosexual couples [10,11]. Some studies investigate kin relationships using photo albums that span a long time window of several years or even decades [12,13].…”
Section: Background and Related Workmentioning
confidence: 99%
“…Several works address investigation of social relations based on such universally valid implicit cues as the age difference between parents and children or the opposite genders of heterosexual couples [10,11]. Some studies investigate kin relationships using photo albums that span a long time window of several years or even decades [12,13].…”
Section: Background and Related Workmentioning
confidence: 99%
“…Thus, Cheng et al (2011) analysed a large pool of public travel photos taken by tourists at a number of popular destinations and applied a face detection technique to extract from those photos certain details about the tourists (namely, their age, gender, and race), which allowed them to discover travel preferences of different categories of tourists and to build a tourist recommendation model 6 . In a follow-up study 8 , they showed how social relationships could also be identified from analysing group photos, which could be applied to personalise group recommendation services. In another example, Tsai & Chung (2012) leveraged the use of the RFID technology to track the behaviour of a theme park's visitors for identifying route patterns that were matched to the input the visitors provided, so that a route recommendation system was built that suggested the newly arrived visitors the most suitable visit programme based on the experience of previous visitors with similar profiles 7 .…”
Section: Recommender Systems For Touristsmentioning
confidence: 99%
“…There are two main directions in this line of work -2D approaches that directly translate image based features into concepts, and 3D approaches that translate detected faces into the 3D scene and then derive features from the 3D layout. Examples of 2D approaches include [5] in which authors predict pairwise relationships e.g., couple, sibling etc. from facial attributes and face subgraphs, and [19], in which authors label pairs of people with a physically-based touch codes such as Hand-hand, Hand-torso etc.…”
Section: Related Workmentioning
confidence: 99%
“…A number of research groups [19,5,10,9] have conducted insightful studies for understanding people interactions in images and videos, though with limited scope. Most of these approaches [19,5] perform their analysis in the 2D camera space.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation